1996
DOI: 10.1366/0003702963904458
|View full text |Cite
|
Sign up to set email alerts
|

Direct Quantitative Analysis from Thin-Layer Chromatography Plates Using Matrix-Assisted Laser Desorption/Ionization Mass Spectrometry

Abstract: Direct quantitative analysis using thin-layer chromatography (TLC) coupled with matrix-assisted laser desorption/ionization mass spectrometry (MALDI) has been demonstrated. An internal standard and a data collection protocol were used for analysis directly from TLC plates to compensate for shot-to-shot signal degradation, as well as deviations of analyte and internal standard spatial distributions within the TLC spot. Cocaine hydrochloride was used as a model compound for this study, and cocaine- d3 was used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 19 publications
1
44
0
Order By: Relevance
“…This combination of pores was not completely new, because the significant effect of similar morphologies has long been recognized in studies concerning heterogeneous catalysts. Nir and Pismen (1977) were probably the first who discovered the enhancement of catalyst effectiveness by convection. Rodrigues et al (1992Rodrigues et al ( , 1993 quantified the concept of augmented diffusivity by forced convective flow due to a pressure gradient, and their studies became the key to understanding perfusion chromatography.…”
Section: Convective Mass Transportmentioning
confidence: 99%
See 2 more Smart Citations
“…This combination of pores was not completely new, because the significant effect of similar morphologies has long been recognized in studies concerning heterogeneous catalysts. Nir and Pismen (1977) were probably the first who discovered the enhancement of catalyst effectiveness by convection. Rodrigues et al (1992Rodrigues et al ( , 1993 quantified the concept of augmented diffusivity by forced convective flow due to a pressure gradient, and their studies became the key to understanding perfusion chromatography.…”
Section: Convective Mass Transportmentioning
confidence: 99%
“…Because both TLC and MALDI MS operate with 2D devices/plates, MALDI MS prevailed in direct coupling with TLC. In the mid-1990s, Gusev et al published first demonstration of separations of proteins and peptides using TLC on plain silica layers with MALDI MS detection followed by a series of more specific papers (Gusev et al, 2000(Gusev et al, , 1995aMehl et al, 1997;Nicola et al, 1996;Vermillion-Salsbury et al, 1999). In addition to successful separation and detection, they also found that the detection limit was several orders of magnitude lower than that typical of conventional MALDI and even lower than "classical" UV detection (Gusev et al, 2000).…”
Section: Thin-layer Chromatography Separation and Mass Spectrometric mentioning
confidence: 99%
See 1 more Smart Citation
“…The principal activity in this area has been reported by Nelson et al [1] as well as by Hercules et al [2][3][4][5][6]. In their studies, proteins and peptides were analyzed and the intensities of single peaks were considered.…”
mentioning
confidence: 99%
“…The limit of detection (LOD) was 7 ng/ml and 10 ng/ml for TOF-SIMS and MALDI, respectively. Hercules et al studied the direct coupling of thin-layer chromatography (TLC) with MALDI for the analysis of a cocaine hydrochloride, using cocaine-d 3 as an internal standard [3]. Their rationale for combining TLC with MALDI was based upon TLC being used as a standard method for the analysis of drugs of abuse, while cocaine-d 3 is available as an internal standard, and that quantitative analysis of cocaine by MALDI had been previously demonstrated [4].…”
mentioning
confidence: 99%